Effect of pH on the Synthesis of Silica Sol-Gel Tetraethylorthosilicate-Trimethylchlorosilan (TEOS-TMCS) - Artha Monica Andini; Choiril Azmiyawati; Adi Darmawan (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Sol-gel synthesis of silica employing the co-precursor trimethylchlorosilane (TMCS) and the precursor tetraethylorthosilicate (TEOS) was accomplished. The purpose of this investigation was to ascertain how pH affected the properties of synthetic silica. The synthesized hydrophobic silica was characterized using FTIR, TGA, and GSA to determine the effect of pH adjustment on the functional group characters, thermal properties, and pore morphology. The ratio between TEOS/TMCS was fixed at 75:25 and varied the pH (4, 6, 7, 8, and 10) and the calcination temperature (without calcination, 300℃ and 500℃). FTIR analysis showed that the number of C-H and Si-OH groups in the xerogel decreased with increasing calcination temperature. Xerogel formed at pH 6 provides the highest thermal stability among other pHs. The results from the BET analysis revealed that changes in pH directly affect the physical characteristics of the surface, making the resulting gel network less rigid and more susceptible to shrinkage of pore volume and diameter in the atmosphere. Meanwhile, in an alkaline medium, continuous condensation will occur so that the pore diameter and volume decrease. The high pore diameter and volume imply that pH 7 is ideal for preparing xerogels.